2012
DOI: 10.1111/j.1365-2672.2012.05248.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium- and ROS-mediated defence responses in BY2 tobacco cells by nonpathogenic Streptomyces sp

Abstract: Aims:  The early molecular events underlying the elicitation of plant defence reactions by Gram‐positive bacteria are relatively unknown. In plants, calcium and reactive oxygen species are commonly involved as cellular messengers of a wide range of biotic stimuli from pathogenic to symbiotic bacteria. In the present work, we checked whether nonpathogenic Streptomyces sp. strains could induce early signalling events leading to defence responses in BY2 tobacco cell suspensions. Methods and Results:  We have demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In other studies, treatments with MAMPs such as chitin, induced defense responses in Msk8 cells [ 37 ]. Furthermore, culture filtrates from P. infestans and a species of the bacterium Streptomyces induced changes in pH in potato cells and ROS production in BY-2 cells, respectively [ 17 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, treatments with MAMPs such as chitin, induced defense responses in Msk8 cells [ 37 ]. Furthermore, culture filtrates from P. infestans and a species of the bacterium Streptomyces induced changes in pH in potato cells and ROS production in BY-2 cells, respectively [ 17 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…as biocontrol agent against Pectobacterium spp. [ 17 ]. Another example is the use of Arabidopsis cell suspension cultures for transcriptomic analysis with a focus on phosphoinositide-dependent phospholipase C (PI-PLC) regulated gene expression [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, bacteria can act in a vaccine-like fashion, eliciting non-specific plant defense mechanisms. This effect provides the host with resistance against pathogens via different mechanisms along the plant infection cycle [122][123][124]. Additionally, the use of some strains in the production of insecticides renders and environmentally friendly approach to control pests and disease without the application of synthetic compounds [99,102].…”
Section: Pgp Streptomyces Against Biotic Stressorsmentioning
confidence: 99%
“…Approximately 80% of the known commercial antibiotics used in medicine and agriculture have initially been isolated from actinobacteria, and especially from strains of genus Streptomyces (Sanglier, Haag, Huck, & Fehr, ), that proved to be a rich source of antibiotics. Furthermore, Streptomyces have been reported in several studies as biological control and showed potential to control a wide range of plant pathogenic bacteria, fungi and oomycetes by producing diverse bioactive substances (Baz, Lahbabi, et al, ; Baz, Tran, et al, ; Errakhi, Lebrihi, & Barakate, ; Goudjal, Zamoum, Sabaou, Mathieu, & Zitouni, ; Samri et al, ). These bacteria like many other microorganisms can also promote plant growth by producing phytohormones (Goudjal et al, ), by improved phosphate mobilization (Hamdali, Hafidi, Virolle, & Ouhdouch, ) and by production of siderophores for iron acquisition (Macagnan, Romeiro, Pomella, & Souza, ).…”
Section: Introductionmentioning
confidence: 99%